Statues and Storms: Leading through Change by Max Price (Cape Town: Tafelberg, 2023), 320pp. ISBN: 978-0-624-08776-2. R350.: Review by Linda Chisholm - Chisholm, Linda (New Agenda: SA Journal of Social and Economic Policy, 2024)
Linda Chisholm reviews the memoir of Max Price, previous Vice Chancellor of the University of Cape Town, where he describes his tumultuous second term as the leader of the institution